All-Normal Dispersion Hole-Assisted Silica Fibers for Generation of Supercontinuum Reaching Midinfrared - K. Tarnowski; W. Urbanczyk (IEEE Photonics Journal, 2016)
A design of technologically feasible hole-assisted silica fibers with all-normal dispersion was proposed and optimized for maximum dispersion located, respectively, at 1.55 and 1.97 $μ\text{m} $ . Such fibers allow for efficient supercontinuum generation using erbium- or thulium-doped fs fiber laser as a pump. Nonlinear simulations accounting for fiber loss were performed to find optimum pumping conditions. Our results point to the possibility of coherent supercontinuum generation in silica fibers with a long-wavelength limit reaching midinfrared.